2008
DOI: 10.1007/s00531-008-0368-2
|View full text |Cite
|
Sign up to set email alerts
|

Early Permian plutons from the northern North China Block: constraints on continental arc evolution and convergent margin magmatism related to the Central Asian Orogenic Belt

Abstract: Recent zircon dating identified several late Carboniferous to early Permian hornblende gabbro-diorite-quartz diorite-granodiorite-tonalite-granite plutons in lithological assemblages at the northern margin of the North China Block (NCB) that were previously regarded as Archaean to Palaeoproterozoic. Our geochronological results indicate that emplacement of these plutons was a continuous process during the late Carboniferous to early Permian, from 324 ± 6 to 274 ± 6 Ma, and lasted for at least 50 Ma. In this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
135
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(146 citation statements)
references
References 65 publications
5
135
0
6
Order By: Relevance
“…after subduction has completely stopped (Davies and Blanckenburg, 1995). The Paleo-Asian Ocean was closed along the Solonker-Changchun suture at ~250 Ma, subsequently the region underwent arc-arc and arc-continent collision (Wu et al, 2007;Zhang et al, 2009). Wu et al (2004) have suggested that many Late Triassic mafic-ultramafic intrusions in the region, including the Honqiling 7 intrusion, formed by basaltic magma generated by decompression melting of asthenospheric mantle, similar to our model.…”
Section: An Integrated Ore Genesis Modelsupporting
confidence: 78%
“…after subduction has completely stopped (Davies and Blanckenburg, 1995). The Paleo-Asian Ocean was closed along the Solonker-Changchun suture at ~250 Ma, subsequently the region underwent arc-arc and arc-continent collision (Wu et al, 2007;Zhang et al, 2009). Wu et al (2004) have suggested that many Late Triassic mafic-ultramafic intrusions in the region, including the Honqiling 7 intrusion, formed by basaltic magma generated by decompression melting of asthenospheric mantle, similar to our model.…”
Section: An Integrated Ore Genesis Modelsupporting
confidence: 78%
“…Xiao et al (2003b) proposed that there was southward subduction under a narrow accretionary wedge in front of the North China craton, although without evidence of a continental margin magmatic arc. However, Zhang et al (2007cZhang et al ( , 2008b reported Carboniferous to early Permian hornblende-bearing granitic plutons (324 ± 6-274 ± 6 Ma) that were emplaced in an Andean-type, active continental arc on the northern margin of the North China craton, confirming that southward subduction also contributed to the closure of the Paleo-Asian ocean. From these relations Zhang et al (2008b) concluded that final amalgamation of the Mongolian arc terranes with the North China craton occurred in the late Permian to earliest Triassic.…”
Section: Subduction Polaritymentioning
confidence: 83%
“…In NE China, especially in the central Mongolia, the Permian mafic rocks show geochemical and isotopic features of N-MORBs and E-MORBs, reflecting the existence of oceanic basin at that time (Chen et al, 2012;Li et al, 2015). Permian arc magmatism along the northern margin of the North China Craton suggested a Cordillera-type active continental margin related to subduction of the paleo-Asian Ocean (Zhang et al, 2009). In the Yanbian area, Cao et al (2011) suggested that the subduction of the Paleo-Asian Ocean could last at ca.…”
Section: Geological Backgroundsmentioning
confidence: 99%